The Mediating Role of Alliance Integrated Network in the Relationship between Service Supply Chain Management Practices and the Indonesian Public Healthcare Organizational Performance - Boonsri Suteerachai; Yananda Siraphatthada (International Journal of Supply Chain Management, 2019)
The main aim of the current study is to investigate the relationship between the supply chain management practices and the Indonesian public healthcare organizational performance. Furthermore, the mediating role of alliance integrated network in the relationship between service supply chain management practices and the Indonesian public healthcare organizational performance is also examined. The study aims to overall assess the organizational performance of healthcare sector. The measures of hospital services include, promptness, health care delivery, cost, efficient and effective diagnosis, internal customer satisfaction, treatment, safety, and decrease in process time. Total quality management includes technology, its implementation, managing relationship with the patient, innovation, patient satisfaction, supplier relationship management, efficient service delivery, and speed of recovery. By employing the survey-based methodology, the study has used the SEM-PLS technique to answer the questions raised in current study. This study, which is among the pioneering studies on the current issue will be helpful for policymakers and researchers in examining the link supply chain management practices, alliance integrated network and the Indonesian public healthcare organizational performance.